Analisis Electronic Word Of Mouth, Online Customer Review dan Fear Of Missing Out Terhadap Keputusan Pembelian pada produk Skincare The Originote Di Marketplace Tiktokshop Melalui Tiktok - Nadia Nur Rahmawati; Lilik Indayani; Satrio Sudarso (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study analyzes the influence of Electronic Word of Mouth (E-WoM), Online Customer Reviews, and Fear of Missing Out (FOMO) on purchasing decisions for The Originote skincare products on TikTok Shop. Data from 96 TikTok Shop user respondents in Sidoarjo were collected using a questionnaire and analyzed using multiple linear regression. The results show that E-WoM, Online Customer Reviews, and FOMO have a positive and significant influence on purchasing decisions. These findings indicate that consumers are highly influenced by reviews and recommendations from other users, as well as the urge to stay on top of trends. This conclusion emphasizes the importance of marketing strategies based on social interactions and customer feedback in the digital era.